1999
DOI: 10.1242/jcs.112.6.761
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functions of nucleolin

Abstract: Nucleolin is an abundant protein of the nucleolus. Nucleolar proteins structurally related to nucleolin are found in organisms ranging from yeast to plants and mammals. The association of several structural domains in nucleolin allows the interaction of nucleolin with different proteins and RNA sequences. Nucleolin has been implicated in chromatin structure, rDNA transcription, rRNA maturation, ribosome assembly and nucleo-cytoplasmic transport. Studies of nucleolin over the last 25 years have revealed a fasci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 653 publications
(134 citation statements)
references
References 160 publications
2
130
0
2
Order By: Relevance
“…Remarkably, snoRNPs are depleted from the nucleolus in cells expressing a dominant–negative mutant of SMN [ 26 ], and this implies a role of SMN not only in the biogenesis of snoRNPs, but also in nucleolar architecture/composition. Nucleolin, one of the most abundant non-ribosomal proteins in the nucleolus, critically drives ribosome biogenesis [ 31 , 37 ]. It has been reported that SMN interacts with nucleolin [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, snoRNPs are depleted from the nucleolus in cells expressing a dominant–negative mutant of SMN [ 26 ], and this implies a role of SMN not only in the biogenesis of snoRNPs, but also in nucleolar architecture/composition. Nucleolin, one of the most abundant non-ribosomal proteins in the nucleolus, critically drives ribosome biogenesis [ 31 , 37 ]. It has been reported that SMN interacts with nucleolin [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coherently with its multitasking role, nucleolin also localizes in other subcellular regions, including the plasma membrane [ 35 , 36 ]. Nucleolin has a predicted molecular mass of approximately 77 kDa, while its apparent molecular mass of about 100 kDa has been attributed to multiple phosphorylation in the N-terminal domain [ 37 ]. Nucleolin is also known as an RNA-binding protein able to affect the fate of target mRNAs in multiple ways [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that NCL, with its acidic N-terminus, four RNA binding motifs in the middle, and a glycine/arginine-rich C-terminus, undergoes multiple post-translational modifications, such as acetylation, ADP-ribosylation, glycosylation, methylation, and phosphorylation [ 35 , 36 ] . These modifications affect its migration on SDS gels, giving a band of apparent MW of 120 kDa [ 37 ] . This altered migration is consistent with the migration of the upper band in our experiments ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleolin, as well as another protein of 38 kDa (B23/No38), were commonly related only to nuclei. However, it was demonstrated that the major nucleolar proteins shuttle between the nucleus and the cytoplasm [38,39].…”
Section: Intracytoplasmic Extruded Nuclear Chromatin and Nucleolimentioning
confidence: 99%